Corporate Patenting AI and ML in Healthcare: Regulatory and Ethical Considerations - Dr. Sourabh Sharma, Damodarrao Thakkalapelli (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
As artificial intelligence (AI) and machine learning (ML) increasingly permeate the healthcare sector, the patenting of innovative technologies in this domain raises critical regulatory and ethical questions. This research paper delves into the complex landscape of patenting AI and ML in healthcare, examining the current regulatory frameworks and ethical considerations surrounding intellectual property in medical technologies. Through an in-depth analysis of recent case studies, legal developments, and industry practices, this paper aims to provide insights into the challenges and opportunities presented by patenting AI and ML innovations in the healthcare sector.